Factors influencing sustainable entrepreneurship in fisheries small and medium-sized enterprises in Tanzania - Mwanahimisi A. Salehe; Jennifer K. Sesabo; Nsubili Isaga; Eliaza J. Mkuna (Social Sciences and Humanities Open)
This paper seeks to establish factors influencing sustainable entrepreneurship in Small and Medium-Sized Enterprises in the fishing industry. Quantitative data were collected from 390 Nile perch fishery entrepreneurs in Lake Victoria, Tanzania. Multiple regression analysis was used to establish factors influencing sustainable entrepreneurship and their significant contribution. Results indicated that entrepreneurs have a high level of sustainable entrepreneurial behaviour but perceive a lack of government support. Entrepreneurs’ values, innovativeness, proactiveness, and rules and regulations were found to highly significantly influence sustainable entrepreneurship in the fishery business. On the other hand, firm assets and firm age were found to be only associated with social and environmental practices and not with sustainable entrepreneurship in general. The study recommends an integrated approach that considers entrepreneurial orientation, gender inclusion, values-driven entrepreneurship, educational initiatives, and community engagement for sustainable entrepreneurship in fisheries.